Rituximab for rheumatoid arthritis-related interstitial lung disease: A systematic review and meta-analysis - Tarun Krishna Boppana,; Saurabh Mittal,; Karan Madan,; Anant Mohan,; Vijay Hadda,; Randeep Guleria, (Archives of Rheumatology, 2024)
Objectives: This systematic review and meta-analysis aimed at summarizing the evidence of efficacy and safety of rituximab in rheumatoid arthritis-related interstitial lung disease (RA-ILD). Materials and methods: PubMed and Embase databases were searched until June 22, 2022, to identify studies on RA-ILD treated with rituximab, confined to predefined inclusion and exclusion criteria. A systematic review and meta-analysis were performed on the included studies to assess the overall stabilization or improvement in ILD, changes in percent-predicted (%-predicted) forced vital capacity (FVC), and %-predicted diffusion capacity of lungs for carbon monoxide (DLCO) following rituximab therapy. Results: A total of 15 studies (4 prospective and 11 retrospective studies) were included, with a total of 314 patients. There were 105 (60.7%) females out of 173 subjects for whom sex details were available from seven studies. The overall pooled proportion of patients with stabilization or improvement in ILD was 0.88 [95% confidence interval (CI): 0.76-0.96, p=0.02]. Rituximab improved FVC from baseline by 7.50% (95% CI: 1.35-13.65; p=0.02, fixed effect). Similarly, rituximab improved DLCO by 6.39% (95% CI: 1.366-14.43; p=0.12, random-effect). Two retrospective studies reported reduced mortality with rituximab therapy compared to tumor necrosis factor-alpha inhibitors. Conclusion: Treatment with rituximab in RA-ILD was associated with a significant improvement in %-predicted FVC, as well as stabilization or improvement in ILD after one year of treatment.